Textbook Analysis On "Effective Communication" English Textbook Based On Rajan's Perspective - Solekah, Musabani Yati, Drs. Djoko Srijono, M.Hum, Nur Hidayat, M.Pd (2014)
In this research, the writer focuses in textbook analysis on "Effective Communication" English textbook based on Rajan's perspective. The writer uses documentary analysis as a method of collecting data. The data source is the textbook entitled "Effective Communication" an integrated course of English for vocational high school published by Pusat Perbukuan Departemen Pendidikan Nasional in 2008 and developed by Aneka Ilmu. The data of the textbook were analyzed by steps; describing the content of the textbook, describing kind of Rajan's perspective found in the textbook, giving percentage material found in the textbook based on Rajan's perspective, and drawing conclusion.in impressionistic approach, the writer found 8 out of 11 criteria suggested by Rajan. The result of percentages is 72, 72% or fair. Indepth approach, the writer found in the listening skill material, "Effective Communication" English textbook has 7 out of 11 criteria suggested by Rajan. The result of percentage is 63,63% or fair. In the speaking skill material, "Effective Communication" English textbook has 9 out of 11 criteria suggested by Rajan. The result of percentages is 81, 81 % or good. In the reading skill material, "Effective Communication" English textbook has 10 out of 11 criteria suggested by Rajan. The result of percentages is 90, 91 % or good. In the writing skill material, "Effective Communication" English textbook has 9 out of 11 criteria suggested by Rajan. The result of percentages is 81, 81 % or good. After analyzing the materials in the textbook, the writer found 43 criteria in the textbook. The result of percentages is 78,18 %. It means that the material in the textbook is good material based on Rajan perspective. The cover and Listening skill of the textbook needs more design to get the target language.